Penser l’écriture transitionnelle chez Claude Simon - Sinan Anzoumana (Multilinguales)
The reception of Claude Simon’s literary work has had two tendencies: the Ricardou tendency strictly inscribes the work in the New Novel (French Nouveau roman). The Dällenbach trend, in a broader perspective, sees the work as avant-garde of literary postmodernism. This article examines these two tendencies to achieve this finality: the transcendence, the ductility of the Simonian creation.